BIBLIOGRAPHIC ANALYSIS AND DECISION FACTORS IN THE OPTIMIZATION AND MATHEMATICAL MODELS OF GROUND SOURCE HEAT PUMP SYSTEMS - Zonai, Viktor; Santa, Robert (Journal of Applied Engineering Science, 2025)
Due to the European Union's reinforced efforts in energy conservation, Ground Source Heat Pump (GSHP) systems have become a prominent technology for improving energy efficiency and environmental sustainability. These systems, which exploit stable underground temperatures for heating and cooling, are leading the charge in reducing energy consumption. However, the mathematical models used to predict the performance of GSHP systems are still under development and frequently overlook local geological and climatic variations. This oversight can lead to significant inaccuracies in the systems' design and efficiency. This study aims to enhance the mathematical modelling and optimization of GSHP systems to improve their operational efficiency and predictive accuracy. By conducting a comprehensive bibliometric analysis of the existing literature using the Web of Science database and VOSviewer software, the research maps the evolution of GSHP technology over the past decade, identifying key research centres and emerging trends.  The findings from the analysis indicate a robust linkage between the optimization and mathematical modelling efforts within the field, highlighting an increasing focus on integrating renewable energy sources to bolster system efficiencies. Prominent institutions and significant publications have been identified, reflecting a shift towards more sustainable and energy-efficient solutions. The study concludes that refining the mathematical models of GSHP systems is crucial for optimizing their performance and sustainability. It emphasizes the necessity for models that can accurately reflect local environmental conditions. Moreover, the research supports continued collaboration between academia and industry to further develop and apply GSHP technology. Future research directions should aim to address the technological and market challenges to enable wider adoption and integration of these systems into existing energy framework.
Keywords: bibliometric analysis, ground source heat pump, mathematical modelling, optimization, environmental sustainability